2010
DOI: 10.1007/s10342-010-0459-z
|View full text |Cite
|
Sign up to set email alerts
|

Transpiration of a hybrid poplar plantation in Saxony (Germany) in response to climate and soil conditions

Abstract: The aim of this study was to investigate transpiration and its main driving factors on the example of a hybrid poplar plantation with the clone Populus maximowiczii 9 P. nigra, cv. Max 1 on a site in the hilly loess region of Saxony (Germany). Transpiration was measured using sap flow techniques during the 2007 and 2008 growing season. At the same time, throughfall, soil moisture dynamics and soil physical properties were also measured. Total transpiration rates amounted to 486 mm and 463 mm, respectively, dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
43
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 39 publications
10
43
1
2
Order By: Relevance
“…The daily average maximum E c value and even the highest daily E c value obtained by genotype Grimminge were within the range of 4.8–10.7 mm/day reported for poplar stands of different genotypes, stand age, and locations in temperate regions of Europe (Fischer et al., 2013). Similar E c values (average and maximum of 2.2 and 6.7 mm/day, respectively) to those displayed in the present study were reported for a poplar plantation of P. maximowiczii  ×  P. nigra using the THB method for measuring sap flow (Petzold et al., 2011). The total canopy transpiration of our study (441 mm/year on average) can only be compared with the transpiration results reported for a poplar plantation in Germany (Petzold et al., 2011) using sap flow measurements (THB method) throughout the growing season (475 mm/year), although the differences among genotypes were notable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The daily average maximum E c value and even the highest daily E c value obtained by genotype Grimminge were within the range of 4.8–10.7 mm/day reported for poplar stands of different genotypes, stand age, and locations in temperate regions of Europe (Fischer et al., 2013). Similar E c values (average and maximum of 2.2 and 6.7 mm/day, respectively) to those displayed in the present study were reported for a poplar plantation of P. maximowiczii  ×  P. nigra using the THB method for measuring sap flow (Petzold et al., 2011). The total canopy transpiration of our study (441 mm/year on average) can only be compared with the transpiration results reported for a poplar plantation in Germany (Petzold et al., 2011) using sap flow measurements (THB method) throughout the growing season (475 mm/year), although the differences among genotypes were notable.…”
Section: Discussionmentioning
confidence: 99%
“…Similar E c values (average and maximum of 2.2 and 6.7 mm/day, respectively) to those displayed in the present study were reported for a poplar plantation of P. maximowiczii  ×  P. nigra using the THB method for measuring sap flow (Petzold et al., 2011). The total canopy transpiration of our study (441 mm/year on average) can only be compared with the transpiration results reported for a poplar plantation in Germany (Petzold et al., 2011) using sap flow measurements (THB method) throughout the growing season (475 mm/year), although the differences among genotypes were notable. Genotypes Bakan and Koster transpired 30% less (340 mm/year on average) and Grimminge 30% more (618 mm/year) than the genotypes in the study of Petzold et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this method requires expensive equipment and only provides a local estimate of evapotranspiration. ET can also be calculated by sap flow rates that are strongly related to transpiration; the aquifer transpiration by an individual tree can be estimated and scaled to the stand level (Allen et al, 1999;Boronina et al, 2005;Meiresonne et al, 1999;Petzold et al, 2010;Zhang et al, 1999). Additionally, ET can be simulated by water balance modelling.…”
mentioning
confidence: 99%